Internet connectivity among people experiencing poverty and deprivation - Wise, Sarah (Journal of Telecommunications and the Digital Economy, 2020)
Access to the digital world can have a positive impact on people’s standard of living, life capabilities, sense of inclusion and wellbeing, and is fast becoming an ‘essential of life’ in developed countries. While the majority of Australians enjoy the benefits that access to the Internet can provide, millions are still missing out on important online services and opportunities. In-depth research is starting to uncover a range of factors that can influence digital inclusion among non-users of the Internet generally. Results from a 2013 Hardship Survey show the disparity in Internet connectivity between people experiencing poverty and deprivation and Australians generally. The paper presents detailed findings from the survey on Internet connectivity. It concludes with suggestions to enhance smartphone usage that might help bridge the ‘digital divide’ for this population subgroup.